Efektivitas Media Interaktif Berbasis Digital dalam Pembelajaran Bahasa Arab Untuk Siswa MI - Safitri, AuliaSofia; Alfattunisa, AuliaRahmah; Afifah, AuliaNur; Abdullah, DanySyarifudin; Mardani, Dadan (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
This study aims to evaluate the effectiveness of using digital-based interactive media in the Arabic language learning process for students at the Madrasah Ibtidaiyah (MI) level. The main focus of this research is to identify its contribution to the field of MI teacher education. The background of this research stems from various challenges in Arabic language learning at the MI level, which is often constrained by the limitations of traditional learning media that are less interesting and not interactive enough for students. Along with the development of digital technology, digital-based interactive media emerged as a promising alternative to increase students' interest, engagement, and understanding in Arabic language learning. This research was conducted using the literature study method, in which data was obtained through analyzing relevant literature, such as scientific journals, books, and previous research reports. This method aims to explore concepts, theories, and best practices related to the use of digital interactive media in Arabic language learning in MI. This study covers various aspects, such as the characteristics of digital interactive media, how to apply it in learning, and its impact on student learning outcomes. This study is expected to provide a deeper insight into the effectiveness of digital-based interactive media in improving the quality of Arabic language learning in MI. In addition, this research also provide.